Assessing the landscape of percutaneous coronary chronic total occlusion treatment in Belgium and Luxembourg: the Belgian Working Group on Chronic Total Occlusions (BWGCTO) registry. Issue 5 (3rd September 2018) - Maeremans, Joren; Kayaert, Peter; Bataille, Yoann; Bennett, Johan; Ungureanu, Claudiu; Haine, Steven; Vandendriessche, Tom; Sonck, Jeroen; Scott, Benjamin; Coussement, Patrick; Dendooven, Daniël; Pereira, Bruno; et al.
Abstract: Background: Important developments in materials, devices, and techniques have improved outcomes of chronic total occlusion (CTO) percutaneous coronary intervention (PCI), and resulted in a growing interest in CTO-PCI. The Belgian Working Group on Chronic Total Occlusions ( BWGCTO) working group aims to assess the evolution within the CTO-PCI landscape over the next years. Methods: From May 2016 onwards, patients undergoing CTO-PCI were included in the BWGCTO registry by 15 centres in Belgium and Luxemburg. Baseline, angiographic, and procedural data were collected. Here, we report on the one-year in-hospital outcomes. Results : Over the course of one year, 411 procedures in 388 patients were included with a mean age of 64 ± 11 years. The majority were male (81%). Relatively complex CTOs were treated (Japanese CTO score =2.2 ± 1.2) with a high procedure success rate (82%). Patient- and lesion-wise success rates were 83 and 85%, respectively. Major adverse in-hospital events were acceptably low (3.4%). Antegrade wire escalation technique was applied most frequently (82%). On the other hand, antegrade dissection and re-entry and retrograde strategies were more frequently applied in higher volume centres and successful for lesions with higher complexity. Conclusion: Satisfactory procedural outcomes and a low rate of adverse events were obtained in a complex CTO population, treated by operators with variable experience levels. Antegrade wire escalation was the preferred strategy, regardless of operator volume.